DMSO-tolerant ornithine decarboxylase (ODC) tandem assay optimised for high-throughput screening - Mingu Gordon Park; Suyeon Yellena Kim; C. Justin Lee (Taylor & Francis Group, 2023)
Ornithine decarboxylase (ODC), the first rate-limiting enzyme in polyamine synthesis, has emerged as a therapeutic target for cancer and Alzheimer's disease (AD). To inhibit ODC, α-difluoromethylornithine (DFMO), an irreversible ODC inhibitor, has been widely used. However, due to its poor pharmacokinetics, the need for discovery of better ODC inhibitors is inevitable. For high-throughput screening (HTS) of ODC inhibitors, an ODC enzyme assay using supramolecular tandem assay has been introduced. Nevertheless, there has been no study utilising the ODC tandem assay for HTS, possibly due to its intolerability to dimethyl sulfoxide (DMSO), a common amphipathic solvent used for drug libraries. Here we report a DMSO-tolerant ODC tandem assay in which DMSO-dependent fluorescence quenching becomes negligible by separating enzyme reaction and putrescine detection. Furthermore, we optimised human cell-line-based mass production of ODC for HTS. Our newly developed assay can be a crucial first step in discovering more effective ODC modulators than DFMO.